Greek Traditional Dances: A Way to Support Intellectual, Psychological, and Motor Functions in Senior Citizens at Risk of Neurodegeneration - Douka, Styliani; Zilidou, Vasiliki I.; Lilou, Olympia; Tsolaki, Magda (Frontiers in Aging Neuroscience, 2019)
One of the major problems that elderly people are facing is dementia. For scientist’s dementia is a medical, social and economic problem, as it has been characterized as the epidemic of the 21st century. Prevention and treatment in the initial stages of dementia are essential, and community awareness and specialization of health professionals are required, with the aim of early and valid diagnosis of the disease. Activities are recommended to the senior citizens to improve their physical and mental health. Dance has been suggested as an appropriate recreational activity for the elderly that brings functional adjustments to the various systems of the body, psychological benefits, and makes exercise to seem interesting and entertaining as it combines the performance of multiple animations with musical accompaniment. A Greek traditional dance program was performed where our sample consisted of 30 healthy elderly and 30 with Mild Cognitive Impairment - MCI. It lasted 24 weeks, two times a week for 60 minutes. Specific traditional dances from all over Greece were selected. The dances were of a moderate intensity at the beginning with a gradual increase in intensity, according to the age and physical abilities of the participants. The results showed a significant improvement in: attention (S4viac-Healthy: z=-3.085, p=0.002; MCI: z=-3.695, p<0.001, S4viti-Healthy: z=-2.800, p=0.005; MCI: z=-3.538, p<0.001), anxiety (Healthy: z=-2.042, p=0.041; MCI: z=-2.168, p=0.030), verbal fluency for MCI (Verflx: t=-2.396, df=29, p=0.023, Verfls: t=-3.619, df=29, p=0.001, Verfmo: t=-3.295, df=29, p=0.003) and in executive functions (FUCAS: z=-2.168, p=0.030). Significant improvement also showed in physical condition (Arm curl– Healthy: z=-3.253, p=0.001; MCI: z=-3.308, p=0.001, Chair stand – Healthy: t=-3.232, df=29, p=0.003; MCI: t=-2.242, df=29, p=0.033, Back scratch– Healthy: z=-1.946, p=0.052; MCI: z=-2.845, p=0.004, Two minute step– Healthy: z=-2.325, p=0.020; MCI: z=-2.625, p=0.009, FootUpandGo– Healthy: z=-4.289, p<0.001; MCI: z=-3.137, p=0.002, Sit and Reach: z=-3.082, p=0.002, Balance on One leg: z=-3.301, p=0.001) and Quality of life (Healthy: z=-1.937, p=0.053; MCI: z=-2.130, p=0.033). This study proves that dancing not only improves the cognitive and physical condition of the elderly but also contributes to a better quality of life.